AN ANALYSIS OF ENGLISH LANGUAGE INTEREST AMONG STUDENTS AT MA NURUL ULUM MERTAK TOMBOK - Galih Purbaya Sakti; Muhamad Suhaili (Sinar Lima, 2026)
This study aimsed to analyze students’ interest in learning English at MA Nurul Ulum Mertak Tombok. The research used a quantitative descriptive method. The participants were students of MA Nurul Ulum Mertak Tombok selected through purposive sampling. Tehnique data were collected using a questionnaire based on a Likert scale and were supported by classroom observation. The collected data were analyzed using descriptive statistical analysis.The findings of this study show that the students’ interest in learning English at MA Nurul Ulum Mertak Tombok is at a moderate level. Several internal factors, such as motivation, attitudes, and self-confidence, influence students’ interest in learning English. In addition, external factors, including teaching methods, learning environment, and teacher support, also contribute to shaping students’ interest. These results indicate that improving instructional strategies and creating a supportive learning environment can help increase students’ interest in learning English.